DEVELOPMENT OF MATERIAL MONITORING SYSTEM ON BOGIE WORKSHOP WITH WEB-BASED APPLICATION - Setiawan, Bayu
In the manufacturing industry, materials are an important part of the production process because they are items of the product to be made. The availability of materials is very important to be monitored and maintained so that the amount is appropriate. Industry 4.0 concept is adopted to improve connectivity between production elements. Improved connectivity serves to accelerate the exchange of data and information between production elements. The rapid exchange of data and information aims to achieve flexibility and increase production efficiency. The concept of Industry 4.0, namely the cyber-physical system (CPS) will be a solution that connects between production elements to be able to simplify and speed up the process of monitoring the availability of materials. In this undergraduate research, a CPS-based system is developed and designed using a web-based application. The web-based application is developed with the aim of carrying out the material monitoring process at the PMK Bogie workshop. Material monitoring will be recorded and sent to a database which is then processed and displayed again through the application. In this study, the concept of a configurable virtual workstation (CVWS) is adopted to suit the industry in Indonesia. This study uses test data for the Bogie MG Bangladesh order. The designed application is divided into 4 parts to support each role in the PMK Bogie workshop. The roles consist of Admin, Production and Planning Control (PPC), Warehouse, and Workstation. In the implementation of Industry 4.0 concept, a web-based application is used. Application testing is done by proving that the application successfully meets the specified design requirements.